THE ROLE OF VENTURE CAPITAL IN THE DEVELOPMENT OF THE SME SECTOR - Đalić, Irena; Terzić, Svetlana; Novarlić, Boris (The European Journal of Applied Economics, 2017)
Entrepreneurs as well as SMEs, regularly face the problem concerning access to finance. Entrepreneurial firms face two major problems. The first concerns access to finance, which places particular restraint on a firm’s ability to increase the level of technology in their business. The second problem is access to know-how. The subject of this survey is the role of venture capital funds in the development of newly established companies and its potential application in the Republic of Srpska. In the Anglo-Saxon countries, newly emerged enterprises that start their business from scratch are called start-up companies. The assumption that venture capital financing can give newly established companies bigger chances of succeeding in their start-up stage is made. It is known that our companies provide capital through bank loans which have lately become less available especially to early stage businesses. Therefore, in order for companies to achieve their goals and develop their projects they must finance their business through venture capital funds that are willing to invest in start-up companies.